2007
DOI: 10.1002/jez.b.21209
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of female mole ovotestes evidences high plasticity of mammalian gonad development

Abstract: Previous studies of the reproductive biology and genetics of European moles (Talpa spp.) showed that all females of these species have ovotestes (gonads with testicular and ovarian tissue) instead of normal ovaries, a unique specialization among mammals. Females are fertile as their ovarian tissue is fully functional. Testicular tissue is abnormal and sterile, but produces high levels of testosterone. This phenomenon also characterizes other talpid species from Europe and North America. To study the origin of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 28 publications
(32 reference statements)
1
23
0
6
Order By: Relevance
“…By contrast, it has been reported that some American mole species lack ovotestes, although they have a masculinised body including a penile clitoris, as described in moles with ovotestes [Rubenstein et al, 2003]. Similarly, not all Asian mole species have ovotestes [Carmona et al, 2008]. However, in most cases it is not known whether female moles without ovotestes are also territorial.…”
Section: In What Direction Is the Mammalian Ovary Evolving?mentioning
confidence: 72%
See 4 more Smart Citations
“…By contrast, it has been reported that some American mole species lack ovotestes, although they have a masculinised body including a penile clitoris, as described in moles with ovotestes [Rubenstein et al, 2003]. Similarly, not all Asian mole species have ovotestes [Carmona et al, 2008]. However, in most cases it is not known whether female moles without ovotestes are also territorial.…”
Section: In What Direction Is the Mammalian Ovary Evolving?mentioning
confidence: 72%
“…This suggests that the cause for the maintenance of regionalised ovaries in a particular species is probably not phylogenetic but adaptive. In the case of moles, Carmona et al [2008] have proposed that the testosterone produced by the testicular portion of the ovotestis during the non-breeding season could foment the aggressive behaviour of females, which have to defend their territories as males do. The mechanism by which testosterone induces aggressive behaviour, through the activation of the aromatase enzyme, which converts testosterone into estrogen in the brain, has been recently reported by Wu et al [2009].…”
Section: In What Direction Is the Mammalian Ovary Evolving?mentioning
confidence: 99%
See 3 more Smart Citations